Contributions of the Rural Education Project (PER) - Kenneth Alfredo Cubillo-Jiménez; Urania María Chaves-Murillo (Universidad Nacional, Costa Rica, 2011)
This paper presents the results of the research project "El proceso de formación inicial del Proyecto de Educación Rural (PER)" (creation of the Rural Education Project, PER by its Spanish acronym), conducted between 1984 and 1987 in the Regional Offices of the Ministry of Public Education in San Carlos, Coto and Limón. The Rural Education Project (PER) was implemented by the Center of Research and Teaching in Education (CIDE) of the Universidad Nacional (UNA) aiming at training teachers of single-teacher schools located in rural areas. The objective of our research was to collect the contributions of PER bearing in mind the training processes required today, and considering the success of PER, which was based on the leadership of teachers to promote community progress in rural areas from the classroom, an input to be considered in the new learning processes of Rural Education